2010
DOI: 10.1002/ijc.25149
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplantation in ovarian cancer—the EBMT experience

Abstract: Although preliminary results suggest that allogeneic hematopoietic stem cell transplantation (allo HCT) for ovarian cancer (OC) is a feasible procedure, the low patient number in previous studies had limited ability to evaluate the true benefit of allo HCT in OC. This retrospective multicenter study included 30 patients with OC allografted between 1995 and 2005 to determine the outcome of patients with OC treated with allo HCT. Prior to allo HCT, patients were in complete response (n 5 1), partial response (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Another retrospective multicenter study including 30 OC patients receiving allografts reported that the presence of chronic GvHD was associated with a significantly higher overall survival (OS) rate (17.6 months vs. 6.5 months, P < 0.05). An objective response rate of 50% and TRM of 20% were reported at the end of first year [67]. Median OS was 10.4 months with a median follow-up of 74.5 months (range 16-148 months).…”
Section: Gvt Effect In Refractory Ovarian Cancermentioning
confidence: 98%
“…Another retrospective multicenter study including 30 OC patients receiving allografts reported that the presence of chronic GvHD was associated with a significantly higher overall survival (OS) rate (17.6 months vs. 6.5 months, P < 0.05). An objective response rate of 50% and TRM of 20% were reported at the end of first year [67]. Median OS was 10.4 months with a median follow-up of 74.5 months (range 16-148 months).…”
Section: Gvt Effect In Refractory Ovarian Cancermentioning
confidence: 98%
“…This data supports the existence of a graft-versus-ovarian cancer effect in correlation with GvHD. In another retrospective multicenter study with 30 allografted OC patients, objective response was observed in 50% and TRM was 20% at the end of first year[68]. The median overall survival was 10.4 mo with a median follow-up of 74.5 mo (16-148).…”
Section: Gvt Effectmentioning
confidence: 99%
“…4,10 In patients with certain kinds of solid tumor, cGVHD is associated with long-term survival. 11,12 Although a study of neuroblastoma showed no advantage of GVHD, it should be noted that statistical analysis of relapse evaluating the impact of cGVHD could not be performed because of the low incidence of cGVHD.…”
mentioning
confidence: 99%